Crooked nose correction: an institutional experience - Das, Anandita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Crooked noses pose a particular challenge in nasal reconstruction, even for the most experienced of surgeons, as there is inevitably a combination of functional and aesthetic abnormalities which need to be addressed. Crooked nose deformity is a common presentation in the ENT clinic due to raise in the road traffic accidents. Methods: This was a prospective study conducted in the Department of ENT, GMCH. All the cases of crooked noses presenting to our department was included in the study. The patients were subjected to a proper history and thorough physical examination. Preoperative nasal analysis was done using photography and nasal endoscopy. The type of intervention for each patient and their outcome was analyzed. Results: The majority of the crooked nose was due to blunt force trauma sustained during road traffic accidents (RTA) or during physical violence. In all crooked nose with an external deformity, there is an underlying septal deformity. The aim of the surgery is to achieve an aesthetically pleasing and a physiologically functioning nose. Conclusions: From the present study, we can conclude that the majority of the crooked nose was due to blunt force trauma sustained during road traffic accidents or due to physical violence. Besides having a considerable external deformity, majority of the cases also had functional problems too and this two aspects could be addressed properly by doing a septorhinoplasty.